Faculty diversity and minoritized student outcomes: an analysis of institutional factors - Curtis, John W., author (Colorado State University. Libraries, 2021)
This paper describes an attempt to utilize the US Department of Education's IPEDS census data on faculty employment in a comprehensive quantitative analysis of the association between "faculty diversity" and degree outcomes for minoritized students. The paper first reviews (and critiques) recent calls to diversify the faculty and then reviews some of the published research on minoritized student success. The literature review suggests that existing studies, both qualitative and quantitative, are limited and do not clearly specify the mechanism by which faculty diversity is expected to improve outcomes for minoritized students. The paper first sets the context for the analysis with updated comprehensive tabulations of the trends in bachelor's degree awards and faculty employment, broken out by racial category and type of institution. Given the overrepresentation of African American and Latinx faculty members at minority-serving institutions, the analysis then proceeds to regression models of degrees awarded to students in those two racial categories by predominantly white institutions. The regression models for 2016-17 degree awards indicate that greater representation of African American faculty at PWIs is associated with larger proportions of degrees to African Americans, but the same is not true for Latinx faculty representation. Models of the change in the proportion of degrees awarded over 20 years do not show a statistically significant effect of changes in minoritized faculty representation, likely due to the small amount of change that has actually occurred. The paper describes a number of challenges for the quantitative analysis of institutional "diversity," not least of which is the problematic racial categories available in the data. The paper concludes with a discussion of the limits of the analysis and what it tells us about efforts to diversify the faculty.
ZIP file includes XLSX spreadsheets.
Keywords: academic employment; faculty; diversity; race; gender; equity; minoritized student